The Role of the Adhesion Receptor CD146 and Its Soluble Form in Human Embryo Implantation and Pregnancy - Bouvier, Sylvie; Kaspi, Elise; Joshkon, Ahmad; Paulmyer-Lacroix, Odile; Piercecchi-Marti, Marie-Dominique; Sharma, Akshita; Leroyer, Aurélie S.; Bertaud, Alexandrine; Gris, Jean-Christophe; Dignat-George, Françoise; Blot-Chabaud, Marcel; Bardin, Nathalie (Frontiers in Immunology, 2021)
CD146 is an adhesion molecule essentially located in the vascular system, which has been described to play an important role in angiogenesis. A soluble form of CD146, called sCD146, is detected in the bloodstream and is known as an angiogenic factor. During placental development, CD146 is selectively expressed in extravillous trophoblasts. A growing body of evidence shows that CD146 and in particular, sCD146, regulate extravillous trophoblasts migration and invasion both in vitro and in vivo. Hereby, we review expression and functions of CD146/sCD146 in the obstetrical field, mainly in pregnancy and in embryo implantation. We emphasized the relevance of quantifying sCD146 in the plasma of pregnant women or in embryo supernatant in the case of in vitro fertilization (IVF) to predict pathological pregnancy such as preeclampsia or implantation defect. This review will also shed light on some major results that led us to define CD146/sCD146 as a biomarker of placental development and paves the way toward identification of new therapeutic targets during implantation and pregnancy.